Performance Comparison of Plasmonic Sensors via Ion Reduction and KOH Methods - Ruqaya Shlaga; Alwan Alwan; Mohammed Mohammed (Journal of Applied Sciences and Nanotechnology)
In this work, several types of plasmonic sensors were prepared by different methods (ion reduction method and wet-chemical KOH route) to detect the ultralow anti-CIPRO concentration using AgNPs/PSi SERS-active substrate with AgNPs concentration. The process was optimized to be very effective in detecting CIPRO and to have a high amplification factor (EF). For the deposition of AgNPs with a concentration of 5×10-3 M and the maximum density of hotspot areas, a nanocrystalline silicon sample prepared by the KOH method and an ion reduction technique before etching was used. We tested an AgNPs/PSi SERS substrate, which showed better performance in detecting the CIPRO antibiotic over a range of doses (10-7-10-13 M). XRD, EDX, FESEM and SERS were used to analyze the PSi samples and the AgNP/PSi chemical sensors. The results of the AgNPs/PSi SERS substrates from both methods showed that the ion reduction process was more effective in detecting the CIPRO antibiotics at their lowest concentrations. It was found that the highest EF at salt concentrations of 5×10-3M was 6.3×1012 for the pre-etching method, compared with 7.78×1010 for the KOH method under the same conditions. The results showed that the proposed AgNPs/PSi SERS substrate is an effective method to find CIPRO even at low concentrations, and that CIPRO was localized approximately near the surface. This approach is considered a revolutionary work that has the potential to modify the plasmonic properties of metallic NPs for SERS applications.